Orbital apex syndrome and ophthalmic artery occlusion caused by acute sinusitis - Dan Liao; Xiaoli Yang; Rong Li (BMC Ophthalmology)
Abstract Background Acute sinusitis is a common condition that rarely leads to severe complications like orbital apex syndrome and ophthalmic artery occlusion, which can cause significant vision loss and require prompt diagnosis and treatment. Case presentation A 40-year-old male presented with sudden vision loss and headache. Examination revealed no light perception in the right eye, proptosis, ophthalmoplegia, and ptosis. Imaging showed retinal edema, vascular filling defects, and diminished opacification of the right ophthalmic artery. The patient was diagnosed with right orbital apex syndrome and ophthalmic artery occlusion caused by acute sinusitis. Conclusion Early recognition and intervention are crucial in managing severe complications of acute sinusitis to prevent irreversible visual impairment.